Peculiarities of Forming the Professional Culture of a Mathematics Teacher by Means of Digital Technologies in Higher Education Institutions of Ukraine - Mariana Kovtoniuk; Olena Soia; Olena Kosovets; Liubov Tiutiun (Proceedings of the International Conference on Applied Innovations in IT, 2025)
The article substantiates the professional culture of a mathematics teacher as an integrated dynamic property of a personality that projects his/her general culture in the field of profession, and is a synthesis of mathematical, scientific, methodological and pedagogical cultures of a teacher, realized in a synergistic educational space using digital technologies. The purpose of the article is to carry out a scientific and theoretical analysis of the peculiarities of the formation of the professional culture of a mathematics teacher and a future mathematics teacher, to define the concept of professional culture of a mathematics teacher, to model its main components (mathematical, scientific, methodological and pedagogical cultures), to establish their structure, to select modern digital technologies for the implementation of professional culture, to conduct a pedagogical study in higher education institutions of Ukraine and to outline possible ways of its formation in a post-industrial society. Mathematical culture includes mathematical competencies, mathematical thinking, and mathematical language. Scientific and methodological culture involves scientific research, implementation of innovative teaching and learning methods, development of the author's educational and methodological product. The pedagogical culture of a mathematics teacher is his/her ability to self-analyze, professional development; self-education, self-development, self-management, pedagogical skills; motivation, communication, professional morality, reflection, adaptability to the professional environment. The Spearman's rank correlation coefficient was used to statistically test the research hypothesis. The interpretation of the size of the effect of correlation dependence was performed in accordance with the methodological recommendations of J. Cohen.